Preoperative Anxiety and Postoperative Pain in Patients With Laparoscopic Hysterectomy - Zhang, Lin; Hao, Li-Jun; Hou, Xiao-Lai; Wu, Ya-Ling; Jing, Lu-Shi; Sun, Ruo-Nan (Frontiers in Psychology, 2021)
Objective: This study was designed to investigate preoperative anxiety situations and postoperative pain degree in Chinese patients undergoing laparoscopic hysterectomy and to analyze the related factors of preoperative anxiety and the correlation between preoperative anxiety and postoperative pain to provide a reference for effective postoperative analgesia management. Methods: A total of 100 female patients undergoing laparoscopic hysterectomy were enrolled in this study and randomly divided into two groups (n = 50, each). In group A, the patients were treated with dexmedetomidine and sufentanil for postoperative analgesia. In group B, the patients were treated with sufentanil alone for postoperative analgesia. All patients were evaluated with a self-rating anxiety scale (SAS) 1 day before the operation. The patients’ pain was evaluated using the numerical rating scale (NRS) 1 day after the operation, and data were recorded. Results: In these 100 patients, the highest preoperative SAS score was 48, and the average score was 40.99 ± 4.55 points, which is higher than the norm in China. There were significant differences in preoperative SAS scores among patients with different occupations and previous surgical experience (P < 0.05). There was no significant difference in SAS scores among patients with different education levels (P > 0.05). The postoperative NRS score of group A was significantly higher than that of group B, and the difference was statistically significant (P < 0.05). The correlation coefficients between SAS scores and NRS scores in groups A and B were 0.836 and 0.870, respectively, presenting with a significantly positive correlation. Conclusion: Preoperative anxiety is an important predictor of postoperative pain. Patients undergoing laparoscopic hysterectomy have preoperative anxiety. The degree of anxiety is influenced by the occupation and previous operation experience of the patients, and patients with higher preoperative anxiety have greater postoperative pain. In addition, we should not neglect the management of postoperative pain because of the small trauma of laparoscopic surgery, and dexmedetomidine combined with sufentanil can improve the postoperative analgesic effect.